Identity and research ethos in Indigenous-to-Indigenous planning research - Michelle Thompson-Fawcett (Frontiers in Research Metrics and Analytics, 2023)
As a member of an Indigenous community myself, my research is necessarily undertaken through an emancipatory Indigenist methodological approach. Indigenous methodologies seek to deconstruct Western paradigms of investigation and understandings that perpetuate the invalidation of Indigeneity, and instead attempt to constitute paradigms centred on Indigenous worldviews. However, Indigenous researchers often work with communities that are not their own. In my case, I have collaborated in a small amount of research with Indigenous groups outside of my own country. But, the majority of my research has been with New Zealand Māori communities other than my own. Key for me, has been the development of personal strategies aimed at keeping me culturally safe in my research with other Indigenous communities, while being secure in my own Indigenous identity. I seek to be culturally respectful in the space of others - safeguarding local Indigenous research sovereignty.